Molecular Phylogeny and Morphological Analysis Support a New Species and New Synonymy in Iranian Astragalus (Leguminosae) - Bagheri, Ali (PLoS One, 2016)
As a result of a taxonomic and phylogenetic revision of Astragalus section Hymenostegis we identified a new species of Astragalus from northwestern Iran, namely A. remotispicatus spec. nov., which is described and illustrated here. It is morphologically similar to A. karl-heinzii in possessing a lax inflorescence. Phylogenetic inference of the nuclear ribosomal DNA internal transcribed spacer (ITS) region support A. remotispicatus as a clearly distinct species within the lax-inflorescence group of this section. Also the placement of A. sciureus var. subsessilis was found to be wrong and this taxon should be treated as a synonym within A. kohrudicus.